The best late season peaches profile - Groot,Etiénne (2020)
Abstract This work aimed to determine the best late season peaches profile via a Best Worst Discrete Choice Experiment. The survey was performed in the city of Zaragoza - Spain, in October 2008. In total, 316 people stated their preferences towards late season peaches. On average, a peach produced in the Calanda area with Protected Designation of Origin (PDO), weighting around 254 g and conditioned in normal packaging or in bulk, may be considered the best late season peach. Among different types of analyzed consumers, all preferred peaches with PDO, produced in the Calanda area. Regarding to fruit size, for many types of consumers, the bigger the better. Only for women and consumers over 50 years old, medium size peaches are preferable to the largest ones. In addition to the fruit size, market segmentation should consider the different kinds of packaging.